E-learning Tools For Remote Learning Before And After Movement Control Order In Tamhidi Centre, Universiti Sains Islam Malaysia, USIM - Siti Rubaini Mat; Shahirah Sulaiman; Junaidah Md Din; Nurul Khadijah Mohamad; Latipah Mohd Noor; Afif Arifin; Mohamad Hazwan Abdul Rahman; Mohd Naser Mohd Sabri (USIM Press, 2024)
Vol. 33 No. S4 (2021): ULUM ISLAMIYYAH The Malaysian Journal of Islamic Sciences